A facile hydrothermal etching process to in situ synthesize highly efficient TiO2/Ag nanocube photocatalysts with high-energy facets exposed for enhanced photocatalytic performance. Issue 34 (25th July 2016) - Zhang, Li; Shi, Dichao; Liu, Baocang; Zhang, Geng; Wang, Qin; Zhang, Jun
Abstract : We developed a facile in situ hydrothermal etching process for synthesizing TiO2 /Ag nanocubes with active high-energy facets exposed and surface plasmon resonance effect for enhanced visible-light-driven photocatalysis. Abstract : A facile hydrothermal etching process was developed to synthesize TiO2 /Ag nanocubes for enhanced photocatalytic application. The synthesis was carried out by chemically etching hollow @TiO2 spheres in the presence of an AgF or AgF/NaF solution under hydrothermal conditions. Utilizing F − as a morphology-directing agent and Ag + as an Ag source during the etching process, TiO2 nanocubes can be easily formed with their active high-energy facets exposed and Ag nanoparticles can be in situ deposited simultaneously on the surface of the TiO2 nanocubes to generate hybrid TiO2 /Ag nanocubes. The resulting TiO2 /Ag nanocubes were well controlled with Ag nanoparticles uniformly distributed on the surface of the TiO2 nanocubes. The morphologies of TiO2 /Ag can be altered from ellipsoidal to cubic shapes depending on the amounts of AgF or AgF/NaF used for chemical etching. Due to the exposure of the active high-energy facets of TiO2 and the uniform deposition of Ag nanoparticles, the obtained TiO2 /Ag nanocubes showed superior catalytic performance for the photocatalytic degradation of rhodamine B under visible-light radiation. It is proposed that the surface plasmon resonance effect arisen from Ag nanoparticles on TiO2 nanocubes can effectively enhance the visible-light driven photocatalytic properties of TiO2 /Ag photocatalysts. Meanwhile, due to the etching of F ions during the synthetic process, the morphology variation of TiO2 from spherical to cubic shapes may be beneficial to the exposure of high energy 001 facets, which is liable to produce more electron–hole pairs in the photocatalytic process, and electron–hole pairs can combine with OH − to produce large amounts of hydroxyl radicals, eventually accelerating the decomposition of the organic dye.